Bioinspired and green water repellent finishing of textiles using carnauba wax and layer-by-layer technique. Issue 8 (2nd August 2020) - Bashari, Azadeh; Salehi K., Amir H.; Salamatipour, Niloofar
Abstract: An attempt was made to deposit a natural based water repellent nano-coating as a green alternative to C8 fluorochemicals compounds, onto different fabrics using a layer-by-layer self-assembly approach. The cubic nanoparticles with average size about 290 nm were synthesized from carnauba via the solvent-free emulsion and melt-dispersion. The negative charge of particles have been approved through zeta potential test (−16.6 mV). Chitosan as a positive charge component used for making bilayers. The contact angles against water for cotton, nylon and nylon/cotton samples were 130.9, 131.4 and 135.0 and 101.7, 102.4 and 124.9 degree after washing. This method have not negative effect on air permeability and fabric handle (The percentage of increase in bending length of treated cotton, nylon and nylon/cotton samples compared to untreated samples were 5.89, 9.52 and 8.76 %). The treated fabrics had antibacterial effect against E.coli and S.aureus bacteria because of the presence of chitosan.